Who Supplies PPP Loans (and Does It Matter)? Banks, Relationships, and the COVID Crisis - Li, Lei; Strahan, Philip E. (Journal of Financial and Quantitative Analysis, 2021)
Abstract We analyze the bank supply of credit under the Paycheck Protection Program (PPP). The literature emphasizes relationships as a means to improve lender information, which helps banks manage credit risk. Despite imposing no risk, however, the PPP supply reflects traditional measures of relationship lending: decreasing in bank size and increasing in prior experience, commitment lending, and core deposits. Our results suggest a new benefit of bank relationships: They help firms access government-subsidized lending. Consistent with this benefit, we show that the bank PPP supply, based on the structure of the local banking sector, alleviates increases in unemployment.